2017
DOI: 10.1080/10942912.2017.1362433
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of crystals of retrograded starch with sharp X-ray diffraction peaks made by recrystallization of amylose and amylopectin

Abstract: Retrogradation is a common occurrence of starchy food and many methods have been tried to retard it. Uncovering the crystalline structure of retrograded starch provides us the necessary information to get an effective method. In this paper, the crystals of retrograded sweet potato starch with sharp X-ray diffraction peaks were obtained by blending sweet potato amylose and amylopectin with narrow distribution of molecular weight. The 2θ angles of those crystals were at 14.7°, 20.7°, 24.3°, 26.5°, and 29.9°. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 43 publications
(53 reference statements)
3
17
0
Order By: Relevance
“…Moreover, in HS the double helical order of the modified starches, including the order of double helices located inside of the crystallites and those located out-side of the crystalline register, [19,27] affected its resistance to enzymatic digestion. The higher RS contents of autoclaved HS (Table 1) are congruent with the widely accepted idea that amylose is the main molecular component of RS obtained during the reorganization of gelatinized starch; [4] however, since amylose can cocrystallize with amylopectin, [26] the contribution of amylopectin to the RS formation needs to be further studied, especially considering the structural complexity of autoclaved starch systems.…”
Section: Relationship Vetween Rs Content and The Structure Of Autoclasupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, in HS the double helical order of the modified starches, including the order of double helices located inside of the crystallites and those located out-side of the crystalline register, [19,27] affected its resistance to enzymatic digestion. The higher RS contents of autoclaved HS (Table 1) are congruent with the widely accepted idea that amylose is the main molecular component of RS obtained during the reorganization of gelatinized starch; [4] however, since amylose can cocrystallize with amylopectin, [26] the contribution of amylopectin to the RS formation needs to be further studied, especially considering the structural complexity of autoclaved starch systems.…”
Section: Relationship Vetween Rs Content and The Structure Of Autoclasupporting
confidence: 79%
“…[ 25 ] During storage of gelatinized starch, amylose, and amylopectin associations occur, involving a recrystallization process. [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Already, the results of the first roentgenographic investigations [3] have revealed that one of the effects of starch structure changes during the retrogradation process is its partial crystallisation. Further studies carried out using both roentgenographic [18,19], NMR [20,21], as well as calorimetric [22,23] methods confirmed this opinion and created foundations for the quantitative characterisation of the retrogradation process on the basis of the phenomenological theory of crystallisation [24]. However, the performed rheological investigations [25][26][27] indicate that despite a certain correlation with changes in the degree of starch system crystallisation, it is the dispersive structure of amorphous regions that decides the mechanical properties of these systems that have important practical significance.…”
Section: Introductionmentioning
confidence: 95%
“…Waxy rice starch generally possesses an A-type crystalline structure, formed via the interaction of amylopectin with short branch-chains and closed branching points [32]. As such, a XRD spectroscopic analysis of rice starches would often show the characteristic diffraction patterns as defined by peaks at 15°, 17°, 18°, 23° and 26° [33].…”
Section: Crystalline Structurementioning
confidence: 99%